Problems of Using Google Classroom as an Instructional Media in Business Administration Students - Urai Makkana, Nipol Ek-udom,Thanuttchayanin Doksroifa,Bundit Anuyahong,Wipanee Pengnate (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The purposes of this study were 1) to investigate problems of using Google Classroom as an instructional media in Business Administration students, and 2) to study additional suggestions from respondents. The research samples were 75 Business Administration students during the second semester of academic year 2021 derived through Simple Random Sampling technique. The instruments for collecting the data were the rating-scale and openended questionnaire. Frequency, percentage, mean, standard deviation and content analysis were used for data analysis. The findings were as follows: the students had a low level of problems of using Google Classroom as an instructional media in overall. When considering each aspect, the lowest rank was Teaching materials, followed by Accessibility and Learning activities; the respondents suggested that using Google Classroom is less effective than a face-to-face meeting; the students are not comfortable with the lack of interaction with other learners or a teacher; the students have several inabilities to work with computers or smartphones; the students have eye strain when learning with Google Classroom; the students have a low internet bandwidth; and the students have too many distractions, e.g., games, social media.